(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The role of agricultural income tax in the revenue of the State is important. During the five-year plan period, we find the increasing tendency of agricultural income tax as seen from 1st five year plan to 6th five year plan. But states like Uttar Pradesh, Bihar, Maharashtra, West Bengal and Rajasthan where zamindari systems have been abolished, the receipt from the tax show a downward tendency. The implementation of land reform measures, i.e, fixation of ceiling and liquidation of larger holdings have affected the yield from the agricultural income tax.